Impact of European Integration on the Functioning of the Insurance Market in Poland - Ratowska-Dziobiak, Eleonora (Comparative Economic Research. Central and Eastern Europe, 2011)
The transformation process, that has begun 20 years ago, generated significant changes in the structure and organization of Polish economy. It stimulated development of particular market's segments, especially of the insurance sector. Poland's accession to the European Union required conformity to Its regulations, fulfillment of several conditions connected with the membership in the European Community. The purpose of this article is to present the main consequences of Poland's integration with EU in the field of insurance market. Joining the common market was an important challenge for this sector in our country.